Preface to a special volume of acarological papers in memory of Ekaterina Alekseevna Sidorchuk (1981–2019) - Zhang, Zhi-Qiang (Zootaxa, 2019)
The acarological and palaeontological communities lost a rising star when Dr Ekaterina Alekseevna (Katya) Sidorchuk passed away in a tragic accident while diving in the Maldives on 20 January 2019. Katya was a good colleague of many acarologists and much-loved friend of numerous collaborators. She was a highly-valued member of the editing team of Zootaxa, serving as a subject editor for Oribatida (Acari) for several years; her excellent editorial contributions were greatly appreciated by many colleagues and friends. To honour Katya, her colleagues and friends of the acarological world dedicate here a special volume of Zootaxa in her memory.